The OMZ and Its Influence on POC in the Tropical Western Pacific Ocean: Based on the Survey in March 2018 - Ma, Jun; Song, Jinming; Li, Xuegang; Wang, Qidong; Zhong, Guorong; Yuan, Huamao; Li, Ning; Duan, Liqin (Frontiers in Earth Science, 2021)
The hypoxia problem in the ocean is worsening, and the oxygen minimum zone (OMZ) continues to expand. The Tropical Western Pacific Ocean is one of the most sensitive areas in response to climate change and human activities, and the OMZ in this area has also expanded significantly. Based on a survey conducted in March 2018, the characteristics of OMZ in the Kocebu seamount area of the Tropical Western Pacific Ocean and its biogeochemical effects are discussed. The results showed that DO in the Kocebu seamount area first decreased and then increased, and the lowest value was 2.49 mg/L at a water depth of 750 m. Based on the oxycline and the threshold of 3.20 mg/L, OMZ in this area was located in the water column of 590-1350 m. With the increase in water depth, the POC concentration decreased gradually and remained stable in the water column deeper than 1000 m. The presence of OMZ reduced the decomposition rate of POC, causing more POC to sink into deeper waters. 38.77% of POC was decomposed in the water column of 150-300 m, whereas only 16.25% of POC was decomposed in the OMZ. In contrast to the vertical distribution of POC, δ13C-POC decreased rapidly in the water columns of 100-150 m and 300-500 m, indicating the rapid decomposition of POC. This result suggests that POC and δ13C-POC should be combined in the evaluation of POC decomposition.